Kinematic analysis of transition phase from underwater to surface swimming in national level swimmers - Stosic, J.; Trinidad, A.; Navarro, E.; Veiga, S. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: The main aim of this study was to describe the kinematical parameters of the transition phase from underwater to surface swimming in national level competitors. Methods: Seventy-four swimmers (33 males and 41 females), all participants in national level championships and at least nine years of training experience (>20 hours per week) were recorded (50 Hz) with two cameras JVC GY-DV500E (from a lateral view) while performing 25 m maximal effort from a push start. Swimmers footage were manually digitized by an experimented observer and calibrated by mean of 2D-DLT algorithms (Abdel-Aziz and Karara, 1971). Some key events (hand(s) separation to hand(s) entry in freestyle, backstroke and butterfly strokes and leg fully flexed to leg fully flexed in breaststroke) from underwater to surface swimming were identified to define the transition phase and the following variables were calculated: transition stroke length (TSL) in meters as the horizontal hip to hip distance, transition stroke rate (TSR) in hertz as the inverse of transition stroke time, and transition velocity (TV) in m/s as TSL divided by transition stroke time. SPSS 20.0 (iBM Corporation, New York, NY, USA) was used to obtain descriptive statistics (mean and standard deviation). Results: Table 1 shows the transition phase kinematical parameters in national-level male swimmers. The freestyle TV was different than from the study by Allnutt (2014) where freestyle TV was 1.62±0.13 m/s (both genders). Similarly, differences were observed with two backstroke TV (1.55; 1.32 m/s) possibly because group data in the study by Allnutt (2014). Freestyle TSL was lower than from study by Vantorre et al. (2010) who measured surface SL between 10 and 12.5 m (i.e. 2.24 ± 0.16 m). Very long TSL in backstroke may be due to supine position of swimmers where resistance to movement is higher (Pease 2013). Freestyle TSR (55.8 stroke/min) was similar as from the study by Vantorre (2010) (i.e. 53.3 ± 4.5 stroke/min). Conclusions: Transition phase cyclic parameters allow evaluating the swimmer's performance during transition from underwater to surface swimming. Velocity and stroke length values were lower than in surface swimming in previous study, indicating technical modifications due to task constraints from underwater to surface position.